2020
DOI: 10.1111/jac.12441
|View full text |Cite
|
Sign up to set email alerts
|

Soya bean (Glycine max L.) evapotranspiration under unlimited and water stress conditions as affected by weather

Abstract: Soya bean's growing area has increased in Hungary since the 2000s, yet few direct field‐based evapotranspiration measurements are available. Compensation evapotranspirometer was used to control two watering levels (unlimited and water stress limited to flowering) at Hungary (45°N), in a three‐season study (2017–2019). Two soya bean varieties with different water demands, Sinara and Sigalia, were analysed. During these vegetation periods, the total evapotranspiration in unlimited water level (both varieties) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…They concluded that the multisource model based on radiation‐intercepted corn quality is suitable for predicting ET0 and corn seed composition (Jiang et al, 2019; Lacerda et al, 2016; Zhang et al, 2021; Schoo et al, 2016). Anda et al, 2020 used a compensation evapotranspirometer to measure evapotranspiration in the field for two Hungarian soybean varieties with different water requirements, sinala, and western bean (Anda et al, 2020). Tuo et al derived the crop evapotranspiration calculation model based on both the energy balance and aerodynamic equations using the SPAC Data.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the multisource model based on radiation‐intercepted corn quality is suitable for predicting ET0 and corn seed composition (Jiang et al, 2019; Lacerda et al, 2016; Zhang et al, 2021; Schoo et al, 2016). Anda et al, 2020 used a compensation evapotranspirometer to measure evapotranspiration in the field for two Hungarian soybean varieties with different water requirements, sinala, and western bean (Anda et al, 2020). Tuo et al derived the crop evapotranspiration calculation model based on both the energy balance and aerodynamic equations using the SPAC Data.…”
Section: Introductionmentioning
confidence: 99%